Proposing Fashion: The Discourse of Glossy Magazines - Moeran, Brian (2013)
This essay discusses the production and discourse of fashion magazines, or glossies, which are an integral part of the ‘fashion system’. As intermediaries between producers and consuming public, the glossies’ main purpose is to propose: to make proposals about what in particular makes the latest clothes ‘fashion’; about what the latest trends are likely to be; about the importance of the names behind them; about reasons why fashion should be important in readers’ lives; and about where the clothes themselves may be purchased. Such proposals legitimize fashion and the fashion world in cultural — and commercial — terms. The glossies make meaningful connections between things that seem to be essentially independent; they give them social lives by creating an imaginary world about them; and they provide historical and aesthetic order in a world whose products, by their very seasonality and potentially chaotic quantity, are likely to go unnoticed. Fashion magazines represent the fashions shown in the catwalk collections. In so doing, they create ‘a discourse of fashion’ whose key evaluative terms are used by different people across time and space to mark out and contest semantic territory in which local cultural preferences engage with globalizing norms of fashion taste.